The dollar yesterday, today, and tomorrow - KINDLEBERGER, C.P. (PSL Quarterly Review, 2013)
For over 20 years the world trading system has been effectively based on a dollar standard. The circulation of the dollar in the world's foreign exchanges is thus of crucial importance to the well-being of the international monetary system. Both shortages and gluts create problems which can inhibit world trade. The author is a leading authority on the dollar and has written extensively on managing its circulation. He presents his views on the reasons for the dollar having gained this role, its present-day problems and future prospects. JEL: E42, F31, F33